(untitled) (Research, Society and Development, 2022)
The objective was to identify the epidemiological profile of patients reported with Leprosy and elucidate education as the main Social Determinant of Health involved. This is an ecological study, descriptive, quantitative and retrospective. It was analyzed the epidemiological profile of patients notified with Leprosy in the municipality of Cascavel-PR from 2007 to 2017, and the relationship between those cases with the educational level through the Compulsory Notification Form’s data. It was found education as an important factor involved in Hansen’s Disease’s illness process. As lower the educational level is, the most amount of the illness was noticed, as so as the sequels found and physical incapacities. The opposite was observed in the group with higher educational levels. Education is a protective factor in Leprosy, as it seems higher the educational level is it can be inferred a better selfcare capacity, based on the concept of functional health literacy, those are more apt as their formation made them capable of interpretate different contexts, as so being able to promote their own health.